Analysis of The Influence of Cooperative Learning With The Teams Games Tournament Model on Students Learning Outcomes - Sudirman, Sudirman; Salomo Leuwol, Ferdinand; Albert , Albert; Maisura , Maisura; Prima Yanuaria Buka , Sisilia (Mudir : Jurnal Manajemen Pendidikan, 2023)
: The objective of this study is to ascertain how the Team Games Tournament instructional strategy affects students' academic success. A quasi-experimental design was used for this study. The participants were chosen using a random selection method. Students from class A, the experimental group, who were taught utilizing the Team Games Tournament learning model, and students from class B, who were instructed utilizing a scientific manner, made up the sample. The data's normality was evaluated using the Shapiro-Wilk method, homogeneity was tested using the Levene method, and the research hypothesis was tested using the Mann-Whitney method. The Mann-Whitney test findings show that a significance level of 0.02, which is less than 0.05, was reached. This demonstrates that the cooperative learning approach known as the TGT (team games tournament) has a significant effect on student learning results.